2012
DOI: 10.1111/j.1365-313x.2012.05121.x
|View full text |Cite
|
Sign up to set email alerts
|

The putative auxin efflux carrier OsPIN3t is involved in the drought stress response and drought tolerance

Abstract: SUMMARYThe phytohormone auxin plays a critical role in plant growth and development, and its spatial distribution largely depends on the polar localization of the PIN-FORMED (PIN) auxin efflux carrier family members. In this study, we identify a putative auxin efflux carrier gene in rice, OsPIN3t, which acts in auxin polar transport but is also involved in the drought stress response in rice. We show that OsPIN3t-GFP fusion proteins are localized in plasma membranes, and this subcellular localization changes u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
125
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 183 publications
(128 citation statements)
references
References 62 publications
2
125
0
1
Order By: Relevance
“…However, OsPIN1 is highly expressed in flowers, and in particular in stamen filaments and at the junction region between anther and filament during late development (Xu et al, 2005). Similarly OsPIN3t , which shows high aminoacid sequence identity to AtPIN3 , is expressed in mature anthers (Zhang et al, 2012). Phenotypic analysis of double and triple OsPIN1 mutant flowers could shed light on the role of these transporters in stamen development.…”
Section: The Role Of Auxin Transport During Early and Late Phases Of mentioning
confidence: 99%
“…However, OsPIN1 is highly expressed in flowers, and in particular in stamen filaments and at the junction region between anther and filament during late development (Xu et al, 2005). Similarly OsPIN3t , which shows high aminoacid sequence identity to AtPIN3 , is expressed in mature anthers (Zhang et al, 2012). Phenotypic analysis of double and triple OsPIN1 mutant flowers could shed light on the role of these transporters in stamen development.…”
Section: The Role Of Auxin Transport During Early and Late Phases Of mentioning
confidence: 99%
“…In contrast, water stress conditions led to an increase in the activity of α-amylase in salt tolerance mechanism. Comparing with adult plant, the mechanisms of stress tolerance in germinating phase are poorly interpreted and might be related to a series of factors that are inherent to the species and environment [26,27].…”
Section: Introductionmentioning
confidence: 99%
“…Although, molecular understanding of the crosstalk between polar auxin transport and drought stress is poorly understood, recent studies have indicated towards involvement of auxin transporters in drought stress. Zhang et al ( 2012 ) showed involvement of auxin effl ux carrier, OsPIN3t, in drought stress response and drought tolerance. Overexpression of OsPIN3t in rice led to upregulation of drought responsive genes, OsDREB2A and OsAP37 , and increased tolerance to drought.…”
Section: Auxin and Drought Stressmentioning
confidence: 99%